Glucose controls the expression of polypyrimidine tract-binding protein 1 via the insulin receptor signaling pathway in pancreatic β cells - Jeong, Da Eun; Heo, Sungeun; Han, Ji Hye; Lee, Eun Young; Kulkarni, Rohit N.; Kim, Wook (Molecules and Cells, 2018)
In pancreatic β cells, glucose stimulates the biosynthesis of insulin at transcriptional and post-transcriptional levels. The RNA-binding protein, polypyrimidine tract-binding protein 1 (PTBP1), also named hnRNP I, acts as a critical mediator of insulin biosynthesis through binding to the pyrimidine-rich region in the 3’-untranslated region (UTR) of insulin mRNA. However, the underlying mechanism that regulates its expression in β cells is unclear. Here, we report that glucose induces the expression of PTBP1 via the insulin receptor (IR) signaling pathway in β cells. PTBP1 is present in β cells of both mouse and monkey, where its levels are increased by glucose and insulin, but not by insulin-like growth factor 1. PTBP1 levels in immortalized β cells established from wild-type (βIRWT) mice are higher than levels in β cells established from IR-null (βIRKO) mice, and ectopic re-expression of IR-WT in βIRKO cells restored PTBP1 levels. However, PTBP1 levels were not altered in βIRKO cells transfected with IR-3YA, in which the Tyr1158/1162/1163 residues are substituted with Ala. Consistently, treatment with glucose or insulin elevated PTBP1 levels in βIRWT cells, but not in βIRKO cells. In addition, silencing Akt significantly lowered PTBP1 levels. Thus, our results identify insulin as a pivotal mediator of glucose-induced PTBP1 expression in pancreatic β cells.
Keywords: Animals; Cell Line, Tumor; Gene Knockout Techniques; Glucose; Heterogeneous-Nuclear Ribonucleoproteins; Humans; Insulin-Secreting Cells; Macaca mulatta; Male; Mice; Mice, Inbred C57BL; Polypyrimidine Tract-Binding Protein; Receptor, Insulin; Signal Transduction; Transfection; Glucose; Insulin; Insulin receptor signaling; Pancreatic β cell; PTBP1